Place Making for Knowledge Generation and Innovation: Planning and Branding Brisbane's Knowledge Community Precincts. Issue 1 (2nd January 2016) - Yigitcanlar, Tan; Guaralda, Mirko; Taboada, Manuela; Pancholi, Surabhi
Abstract: Knowledge generation and innovation have been a priority for global city administrators particularly during the last couple of decades. This is mainly due to the growing consensus in identifying knowledge-based urban development as a panacea for burgeoning economic problems. Place making has become a critical element for success in knowledge-based urban development as planning and branding places is claimed to be an effective marketing tool for attracting investment and talent. This paper aims to investigate the role of planning and branding in place making by assessing the effectiveness of planning and branding strategies in the development of knowledge and innovation milieus. The methodology of the study comprises reviewing the literature thoroughly, developing an analysis framework, and using this framework to analyze Brisbane's knowledge community precincts—namely Boggo Road Knowledge Precinct, Kelvin Grove Urban Knowledge Village, and Sippy Downs Knowledge Town. The analysis findings generate invaluable insights into Brisbane's journey in place making for knowledge and innovation milieus and communities. The results suggest as much as good planning, branding strategies, and good practice, the requirements of external and internal conditions also need to be met for successful place making in knowledge community precincts.